GROWTH RESPONSE OF WHITE SHRIMP (Litopenaeus vannamei) REARED IN LOW SALINITY MEDIUM, FED DIFFERENT PROTEIN AND CALCIUM LEVELS - Erly Kaligis (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The white shrimp (Litopenaeus vannamei) has been an important commercial shrimp species in Indonesia. This species is tolerance to low salinity therefore, it is important to develop its aquaculture. The purpose of this study was to study the effect of protein and calcium levels in diet on growth performance of the white shrimp post larvae. A factorial experiment at three levels of dietary protein (25, 35, 45%) and three levels of calcium (0, 2, 4%) with three replicates were used in this experiment. Fifteen shrimps (PL25) were placed in triplicate 45-l glasses aquarium. Salinity in shrimp aquarium was 2 ppt. The shrimps were fed of about 8% of body weight four times per day for 28 days. Measured parameters were daily growth rate, feed efficiency, RNA/DNA ratio, frequency of moulting, calcium and protein retentions. Results showed that shrimp fed on diet 45% protein and 2% calcium levels produce higher daily growth rate, feed efficiency, RNA/DNA ratio, protein retention, compared to the other treatments. It was concluded that the white shrimp post larvae required 45% protein and 2% calcium for the shrimp maintenance in a low salinity condition. Keywords: protein, calcium, RNA/DNA ratio, moulting, Litopenaeus vannamei